Summary of thermosetting composite material welding. Issue 1 (January 2021) - Cui, X; Tian, L; Wang, D S; Dong, J P
Abstract: Thermosetting composites are widely used in structural parts of aerospace industry. The research of thermosetting composites is also developing continuously, but the connection modes of thermosetting composites needs to be innovative. Mechanical fastening, adhesive bonding and melt welding are the commonly used connections. However, mechanical fastening and adhesive bonding have many disadvantages. Such as drilling, it not only makes fiber fracture, but also destroys composite materials. In adhesive bonding, surface treatment and bonding cycle need a lot of manpower. As time goes by, the bonding strength of the joint gradually decreases. Welding technology has great advantages in assembling and joining thermoset composites (TSC). Different from other review papers, this paper mainly discusses two methods of the surface of the Thermoset composites laminate to be coasted with a thermoplastic layer for the main welding method (resistance welding, ultrasonic welding), Thermoplastic hybrid interlayer and Thermoplastic film co-cure. The problem of thermal degradation of Thermoset composites in welding is discussed.